Respuesta :
Answer:
B) x = 2, y = 1
Step-by-step explanation:
Add the two equations to eliminate the x-variable.
(x +3y) +(-x +6y) = (5) +(4)
9y = 9 . . . . . . .simplify
y = 1 . . . . . . . . divide by 9
You can substitute this value into either equation to find x.
x + 3(1) = 5
x = 2 . . . . . . . . subtract 3
The solution is (x, y) = (2, 1).
Answer:
B) x=2, y=1
Step-by-step explanation:
x+3y=5
-x+6y=4
solve the equation
x=5-3y
-x+6y=4
substitute the value of x into an equation
-1(5-3y)+6y=4
multiply numbers in parenthesis by -1
-5-3y+6y=4
put -5 as positive and add 5 to 4 and put -3y as positive and add to 6y.
9y=9
divide both sides by 9
y=1
substitute the value of y into an equation
x=5-3•1
multiply 3 to 1
x= 5-3
subtract 5 to 3
x=2
------------
x=2
y=1
------------